A Case Report Scaphoid Non-Union Management: With Dual Bone Grafting - Priyanshu; Ankush Mohabey; Samir Dwidmuthe; Amit Surushe; Deepanjan Das (Journal of Orthopaedic Case Reports)
Introduction: Scaphoid non-union (SNU) is a potential complication of scaphoid fractures due to limited blood supply, primarily from the radial artery. The scaphoid’s lack of a periosteum restricts its ability to undergo efficient healing, relying solely on primary bone healing. Case Report: This case report aims to evaluate the management of SNU, particularly in waist fractures with shortening and humpback deformity. It assesses the clinical, radiographic, and functional outcomes of patients treated with bone grafting, utilizing tricalcium phosphate and cancellous bone grafts, contributing to the ongoing discussion on optimal treatment strategies for SNU cases. Conclusion: Learning points of view from this article include: The use of dual bone grafting gives good results in terms of union and patient function. Tricalcium phosphate is an effective augment for autograft in cases of non-union.